PDE5 Overexpression in Well-Differentiated Thyroid Carcinomas Is Associated with Lymph Node Metastasis. (1st October 2017) - Zhang, Ning; Fang, Zeng; Li, Qiufang; Wang, Kebing; Li, Songqi; Li, Wen; Wang, Shenming
Abstract : Overexpression of PDE5 is observed in certain human cancers, but PDE5 expression in well-differentiated thyroid carcinoma (WDTC) is unknown. We therefore examined PDE5 expression and its relationship with the clinicopathological features of WDTC. Real-time qPCR and Western blotting were performed to analyze the expression of PDE5 mRNA and protein in paired WDTC tumor and adjacent nontumor tissues. Immunohistochemistry was used to analyze the expression of PDE5 in paraffin-embedded tissues obtained from 103 cases of WDTC. Statistical analyses were performed to examine the correlation between PDE5 expression and clinicopathological features. The expression of PDE5 mRNA and protein was upregulated in WDTC lesions compared to their paired noncancerous tissues. The expression of PDE5 was significantly correlated with age (P = 0.032 ), regional lymph node status (P = 0.004 ), and the presence of distant metastasis (P = 0.020 ). High PDE5 expression was more closely associated with lymph node involvement in patients over 45 years (OR = 15.60, P ≤ 0.05 ). Thus, PDE5 may be a potential biomarker in WDTC, particularly in patients with regional lymph node metastasis, which is associated with disease recurrence, treatment failure, and morbidity. PDE5 expression may also help predict the prognosis and recurrence of WDTC after surgery.